An eight-year study of Shigella species in Beijing, China: serodiversity, virulence genes, and antimicrobial resistance - Mei Qu; Xin Zhang; Guirong Liu; Ying Huang; Lei Jia; Weili Liang; Xitai Li; Xiaona Wu; Jie Li; Hanqiu Yan; Biao Kan; Quanyi Wang (Journal of Infection in Developing Countries)
Introduction: This study was conducted to determine the prevalence of serotypes, virulence factors, and antimicrobial resistance patterns of Shigella spp. in Beijing, China, from 2004 to 2011. Methodology: Real-time PCR assays were used to detect virulent genes, and the Kirby-Bauer disk diffusion method was used to evaluate antimicrobial resistance. Results: Among the total of 1,652 Shigella isolates, S. sonnei (57.1%) was the predominant species, followed by S. flexneri (42.3%), S. dysenteriae (0.4%), and S. boydii (0.2%). Nineteen serotypes were discovered among S. flexneri strains. The virulence gene ipaH was the most frequent, followed by sen and set. The presence of set showed significant difference in two dominant serogroups, S. flexneri and S. sonnei. Over 90% of Shigella isolates showed resistance to at least three drugs with widened spectrum. High-level antimicrobial resistance to single and multiple antibiotics was more common among S. sonnei than S. flexneri. Conclusion: There was an obvious serotype change and a dramatic increase of antibiotic resistance in Shigella prevalence in Beijing.